OPTIMALISASI PEMANFAATAN MEDIA DIGITAL UNTUK MENINGKATKAN LITERASI DAN NUMERASI DI SMP NEGERI 2 IBUN - Eva Dianawati Wasliman; Ai Citra Susanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the optimization of digital media utilization in improving students’ literacy and numeracy skills at SMP Negeri 2 Ibun. The background of this research is based on the rapid development of digital technology and the increasing demand for quality learning in the digital era. This study employed a descriptive method with a qualitative approach. The research subjects consisted of teachers and students, while data were collected through observation, interviews, and documentation. The results indicate that the use of digital media such as instructional videos, educational applications, and online learning platforms can enhance students’ learning interest, understanding of learning materials, as well as their literacy and numeracy skills. However, the optimization of digital media utilization still faces several challenges, including limited facilities and infrastructure, as well as teachers’ competencies in managing digital-based learning. Therefore, school support in the form of teacher training and adequate facility provision is necessary to ensure the optimal implementation of digital media in improving students’ literacy and numeracy skills.